Prototipo de bajo costo para la automatización de la producción de cannabis medicinal en invernadero apoyado por IoT - Ordoñez-Quintero, Cristian-Camilo; Ordóñez-Erazo, Hugo-Armando; Ordoñez, Armando (Revista Científica, 2022)
Medicinal use of cannabis offers great prospects for producers from an economic point of view and for users in terms of health. However, in order to exploit the full potential of the different varieties of cannabis, it is necessary to create some particular environmental conditions for each type of crop, which is very difficult to achieve by hand. Therefore, various proposals have explored the use of technologies for automating the control of these crops. These solutions are mostly black box, do not allow for customization, and can be very expensive. This article describes a prototype that allows controlling a cannabis greenhouse (through humidity and temperature sensors, among others). The prototype and its usability were evaluated among cannabis producers, with promising results for its use and the production of the designed device and mobile app.